Endobronchial lesion and pericardial extension of pediatric hodgkin lymphoma: A rare concomitant presentation - J T Srikanta; K M Chandan Kumar (Indian Journal of Medical and Paediatric Oncology)
Concomitant endobronchial lesion and pericardial effusion/extension in Hodgkin lymphoma (HL) are extremely rare and can be clinically confused with disseminated tuberculosis or aggressive non-HL changing both management and prognosis. We present a 15-year-old adolescent with complaints of fever, weight loss, and acute onset of cough, chest pain, and breathing difficulty. Computed tomography of the thorax showed moderate-to-significant pericardial effusion/extension with significant mediastinal adenopathy. A bronchoscopy demonstrated a well-defined polypoidal mass lesion in the right upper lobe bronchus. Endobronchial biopsy of the lesion with endobronchial ultrasound/transbronchial needle aspiration of mediastinal lymphadenopathy categorically diagnosed with classic HL.